BUSINESS CYCLES AND FINANCIAL CRISES: THE ROLES OF CREDIT SUPPLY AND DEMAND SHOCKS. (11th February 2014) - Nason, James M.; Tallman, Ellis W.; Kim, Chang-Jin; Morley, James; Piger, Jeremy
<x content-type="archive" xml:space="preserve">Abstract</x> This paper explores the hypothesis that the sources of economic and financial crises differ from those of noncrisis business cycle fluctuations. We employ Markov-switching Bayesian vector autoregressions (MS-BVARs) to gather evidence about the hypothesis on a long annual U.S. sample running from 1890 to 2010. The sample covers several episodes useful for understanding U.S. economic and financial history, which generate variation in the data that aids in identifying credit supply and demand shocks. We identify these shocks within MS-BVARs by tying credit supply and demand movements to inside money and its intertemporal price. The model space is limited to stochastic volatility (SV) in the errors of the MS-BVARs. Of the 15 MS-BVARs estimated, the data favor a MS-BVAR in which economic and financial crises and noncrisis business cycle regimes recur throughout the long annual sample. The best-fitting MS-BVAR also isolates SV regimes in which shocks to inside money dominate aggregate fluctuations.